Pengaruh Implementasi Akreditasi Sekolah dan Kinerja Pembelajaran Guru Terhadap Mutu Pendidikan SMA Negeri Se-Kota Batu - Gusti Ayu Larasati Nur Rohma; Sunarni Sunarni; Desi Eri Kusumaningrum (Universitas Negeri Malang, 2020)
Abstract: The role of education in educating the nation is very important, so it is very important for schools to pay attention to the quality of education. Quality improvement management is considered an important factor, including the assessment of school performance through accreditation so that it will be known how good teacher competence is. Accreditation can be used as a means to ensure school quality. This study aims to determine: (1) the level of school accreditation implementation; (2) the level of teacher learning performance; (3) the level of education quality; (4) the effect of school accreditation implementation and teacher learning performance on education quality. This study used a quantitative approach with descriptive and regression analysis. The results of the study illustrate: (1) The level of school accreditation implementation in SMA Negeri Se-Kota Batu is in the range of 63-76 in the very good category; (2) The level of teacher learning performance in SMA Negeri Se-Kota Batu is in the range of 65-80 in the very high category; (3) The level of education quality in SMA Negeri Se-Kota Batu is in the range of 99-120 in the very good category; (4) There is an influence between school accreditation and teacher learning performance on the quality of education of SMA Negeri Se-Kota Batu with an influence of 77.7%, with details between accreditation variables having an influence on the quality of education of SMA Negeri Se-Kota Batu as much as 3.0%. The influence of teacher learning performance variables on the quality of education. Keywords: Implementation of school accreditation; teacher learning performance; education quality Abstrak: Peran pendidikan dalam mencerdaskan kehidupan bangsa sangatlah penting, maka sangat penting bagi sekolah untuk memperhatikan mutu pendidikan. Manajemen peningkatan mutu dianggap sebagai faktor penting, termasuk dalam penilaian terhadap kinerja sekolah melalui akreditasi sehingga akan diketahui seberapa baik kompetensi guru. Akreditasi dapat digunakan sebagai sarana untuk menjamin mutu sekolah. Penelitian ini memiliki tujuan untuk mengetahui: (1) tingkat implementasi akreditasi sekolah; (2) tingkat kinerja pembelajaran guru; (3) tingkat mutu pendidikan; (4) pengaruh implementasi akreditasi sekolah dan kinerja pembelajaran guru terhadap mutu pendidikan. Penelitian ini menggunakan pendekatan kuantitatif dengan analisis deskriptif dan regresi. Hasil penelitian menggambarkan: (1) Tingkat implementasi akreditasi sekolah di SMA Negeri Se-Kota Batu berada pada rentang nilai 63-76 dalam kategori sangat baik; (2) Tingkat kinerja pembelajaran guru di SMA Negeri Se-Kota Batu berada pada rentang 65-80 dalam kategori sangat tinggi; (3) Tingkat mutu pendidikan di SMA Negeri Se-Kota Batu berada pada rentang 99-120 dalam kategori sangat baik; (4) Terdapat pengaruh antara akreditasi sekolah dan kinerja pembelajaran guru terhadap mutu pendidikan SMA Negeri Se-Kota Batu dengan pengaruh sebesar 77,7%, dengan rincian antara variabel akreditasi mempunyai pengaruh terhadap mutu pendidikan SMA Negeri Se-Kota Batu sebanyak 3,0%. Pengaruh variabel kinerja pembelajaran guru terhadap mutu pendidikan SMA Negeri Se-Kota Batu sebesar 74,7%. Kata kunci: Akreditasi sekolah, kinerja pembelajaran guru, mutu pendidikan